2013
DOI: 10.1007/s12402-013-0114-x
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity and continuity of attention deficit hyperactivity disorder (ADHD) from childhood to adolescence in Turkey

Abstract: The aim of this study was to examine clinical outcomes, psychiatric comorbidity and neuropsychological characteristics in Turkish adolescents with an attention deficit hyperactivity disorder (ADHD) diagnosis in childhood. A total of 45 children with ADHD diagnosis and 28 children with a psychiatric diagnosis other than ADHD in a 1-year cohort of 7-10-year-olds were reevaluated 6 years later using Schedule for Affective Disorders and Schizophrenia for School-Age Children Present and Lifetime version and Wechsle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
10
1
Order By: Relevance
“…Four years later, the comorbidity rate was 75%. This rate was higher than those found in other studies: 46.4% ( 49 ), 46.6% ( 35 ), and 50% ( 13 ). Such differences could perhaps be explained by sample characteristics because in this study the patients were selected from a center specialized in ADHD treatment, a reference in the area, thus potentially composed of patients with more severe forms of the illness and more thus more likely to seek treatment.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Four years later, the comorbidity rate was 75%. This rate was higher than those found in other studies: 46.4% ( 49 ), 46.6% ( 35 ), and 50% ( 13 ). Such differences could perhaps be explained by sample characteristics because in this study the patients were selected from a center specialized in ADHD treatment, a reference in the area, thus potentially composed of patients with more severe forms of the illness and more thus more likely to seek treatment.…”
Section: Discussioncontrasting
confidence: 72%
“…However, almost all of these studies were conducted in clinical samples in North America. Culture can affect different aspects of development, such as language development, behavioral expectations, parental tolerance for non-compliant behaviors, emotional regulation, binding styles, identity formation, motivation, and other aspects of parenting and early childhood education ( 35 ). Therefore, the diagnosis of ADHD and its evolution may be affected by cultural factors.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this observation may be attributed to the fact that more complex and resistant cases are usually referred to tertiary centers (Abd-Elmoneim et al, 2020;Baeyens, Roeyers, D'Haese, et al, 2007) Cohort studies allowed a more precise overview of age effects in concomitant enuresis and ADHD, and support findings of the cross sectional and case control designs (Baeyens, Roeyers, Van Erdeghem, et al, 2007;Cak et al, 2013;Mellon et al, 2013). In spite of that, further cohort studies are required in order to provide more robust evidence, since included studies present limitations such as small samples, heterogeneous control groups and low follow up time (Baeyens, Roeyers, Van Erdeghem, et al, 2007;Cak et al, 2013). One of the reviewed papers, in spite of being a population-based study, was probably not representative of the general population, since the sample included only children from a mainly white, middle class community, which may limit inferences to other populations (Mellon et al, 2013).…”
Section: ) Discussionmentioning
confidence: 80%
“…Three case controls, one cross sectional study and three cohort studies found significant age differences between the analyzed groups (Abd-Elmoneim et al, 2020;Baeyens, Roeyers, D'Haese, et al, 2007;Baeyens, Roeyers, Van Erdeghem, et al, 2007;Cak et al, 2013;Khazaie et al, 2018;Mellon et al, 2013;Robson et al, 1997).…”
Section: 5) Age Differencesmentioning
confidence: 93%
“…Thus we find comorbidity with other disorders and/or impairments, such as substance abuse and Behavior Disorders, along with academic difficulties (Brown, 2005;Cak, Dinc, Tuzun, Evinc, Cop, Cuhadaroglu Cetin, 2013). In this regard, starting school and the ongoing process as a student are usually stressful events, putting students with ADHD in a vulnerable position for experiencing stress.…”
mentioning
confidence: 92%